Analysis of Consumer Food Purchasing Behavior Using Shopeefood Application in Gunungpati Subdistrict, Semarang City - Alfin Muslikhun; Setya Pramono; Garbada Boris Setyawan (MultiTech Publisher, 2023)
This research aims to study how the influence of discounts, ease of use, and ease of payment in influencing the decision to use the ShopeeFood application in Gunungpati District and its surroundings. The population of this study is all residents who live in Gunungpati Subdistrict and its surroundings. While the research sample is residents of Gunungpati and its surroundings who actively use the ShopeeFood application. The sampling technique used purposive sampling method and obtained 50 respondents. The results of hypothesis testing indicate that all discount variables, ease of use and ease of payment have a significant positive effect on the decision to use the ShopeeFood application. The coefficient of determination test shows that the variables of discounts, ease of use and ease of payment can influence the decision to use the ShopeeFood application by 78.7%. While the remaining 21.3% is influenced by other variables